Deficits in Motor Performance, Neurotransmitters and Synaptic Plasticity in Elderly and Experimental Parkinsonian Mice Lacking GPR37 - Zhang, Xiaoqun; Mantas, Ioannis; Fridjonsdottir, Elva; Andrén, Per E.; Chergui, Karima; Svenningsson, Per (Frontiers in Aging Neuroscience, 2020)
Parkinson’s disease (PD) etiology is attributed to aging and the progressive neurodegeneration of dopamine (DA) neurons of substantia nigra pars compacta (SNc). GPR37 is an orphan G-protein Coupled Receptor (GPCR) that is linked to the juvenile form of PD. In addition, misfolded GPR37 has been found in Lewy bodies. However, properly folded GPR37 found at the cell membrane appears to exert neuroprotection. In the present study we investigated the role of GPR37 in motor deficits due to aging or toxin-induced experimental parkinsonism. Elderly GPR37 knock out (KO) mice displayed hypolocomotion and worse fine movement performance compared to their WT counterparts. Striatal slice electrophysiology reveiled that GPR37 KO mice show profound decrease in long term potentiation (LTP) formation which is accompanied by an alteration in glutamate receptor subunit content. GPR37 KO animals exposed to intrastriatal 6-hydroxydopamine (6-OHDA) show poorer score in the behavioral cylinder test and more loss of the DA transporter (DAT) in striatum. The GPR37 KO striata exhibit a significant increase in GABA which is aggravated after DA depletion. Our data indicate that GPR37 KO mice have DA neuron deficit, enhanced striatal GABA levels and deficient corticostriatal LTP. They also respond stronger to 6-OHDA-induced neurotoxicity. Taken together, the data indicate that properly functional GPR37 may counteract aging processes and parkinsonism.